VD_FINDINFO HC / 2014 / 170 vom 13. Februar 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, CONCUBINAGE, MINIMUM VITAL | 163 CC, 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 316 al. 3 CPC (CH), 317 CPC (CH)